2011
DOI: 10.1002/ijc.26242
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and the risks of Barrett's oesophagus: A population‐based case–control study

Abstract: Infection with Helicobacter pylori is associated with significantly reduced risks of oesophageal adenocarcinoma, however few studies have examined the association between H pylori and Barrett's oesophagus (BO), the precursor lesion. We explored the relationship between H pylori infection and BO and sought to identify potential modifiers. We compared the prevalence of positive H pylori serology among 217 adults with simple BO (without dysplasia), 95 with dysplastic BO and 398 population controls sourced from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 50 publications
0
50
0
1
Order By: Relevance
“…Despite the significance of H. pylori as a pathogen, concerns have been raised about the consequences of the loss of an organism that has colonized humans for >100,000 years (Moodley et al, 2012). Observations of inverse associations of H. pylori with diseases include early onset-asthma (Arnold et al, 2011a; Chen and Blaser, 2007, 2008), gastrointestinal (Cohen et al, 2012; Higgins et al, 2011; Rothenbacher et al, 2000) and systemic (Perry et al, 2010) infections, and Barrett’s esophagus and its consequences (Corley et al, 2008; Rubenstein et al, 2014; Thrift et al, 2012). In mice, the age at which H. pylori is acquired is critical in influencing outcomes; challenged adult mice developed pre-neoplastic lesions, but neonatal mice were protected against severe pathology by immune tolerance (Arnold et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of H. pylori as a pathogen, concerns have been raised about the consequences of the loss of an organism that has colonized humans for >100,000 years (Moodley et al, 2012). Observations of inverse associations of H. pylori with diseases include early onset-asthma (Arnold et al, 2011a; Chen and Blaser, 2007, 2008), gastrointestinal (Cohen et al, 2012; Higgins et al, 2011; Rothenbacher et al, 2000) and systemic (Perry et al, 2010) infections, and Barrett’s esophagus and its consequences (Corley et al, 2008; Rubenstein et al, 2014; Thrift et al, 2012). In mice, the age at which H. pylori is acquired is critical in influencing outcomes; challenged adult mice developed pre-neoplastic lesions, but neonatal mice were protected against severe pathology by immune tolerance (Arnold et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal adenocarcinoma derived from BE is not common in Japan as compared with western countries, whereas gastric carcinoma is more prevalent in Japan. This inverse relationship may reflect the high prevalence of H. pylori infection in Japan and the low prevalence in western countries [24,39,40] . Another notable epidemiological difference between these regions is the length of BE; that is, SSBE is common in Japan but LSBE is more prevalent in western countries [27,28,30,31] .…”
Section: Variables Associated With Dysplasia In Sce-type Bementioning
confidence: 99%
“…Thrift et al [87] reported a populationbased case-control study which found that H. pylori infection was inversely associated with BE, whereas there was some variation in the magnitude of risk estimates across strata of age, gender, reflux symptoms, and use of proton pump inhibitors (PPIs) or H 2 -receptor antagonists (H 2 RAs Further studies are needed to test this association, and the studies should enroll patients prospectively to ensure standard BE diagnostic methods, H. pylori detection methods, and overall high study quality.…”
Section: H Pylori Infection and Carcinogenesismentioning
confidence: 99%